Mediated Effects of Social Media Characteristic on Gen Z Job Application Intentions - Ni Made Puja Cista Dewi Puja; Elsye Tandelilin; Andri Rianawati (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2026)
The development of social media has changed corporate strategies in attracting potential employees, especially from Generation Z, who are highly dependent on digital information in making career decisions. The purpose of this study is to examine how social media features affect Generation Z's intention to apply for jobs, taking into account the direct and mediated effects of employer branding, person-organization fit, and corporate reputation. This study uses a quantitative methodology by surveying unemployed final-year students and recent Generation Z graduates in East Java. Data was collected via an online survey, and analysis occurred using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The results show that social media charac…